Case Report: ICIs-induced Guillain–Barré syndrome recovered from mycophenolate mofetil - Ding, Mengge; Deng, Chao; Liu, Xianling; Jiang, Shun; Gao, Yuan; Fan, Dan; Zhou, Yiguang; He, Jiangbo; Liu, Chaoyuan (Frontiers in Immunology, 2023)
The emergence of immune checkpoint inhibitors (ICIs) has significantly prolonged the survival time of cancer patients. However, it may also lead to various immune-related adverse events (irAEs). Guillain–Barré syndrome (GBS) is a rare kind of irAE. Due to the self-limited nature of the disease, most GBS patients can recover spontaneously. But respiratory failure, even death, can occur in severe cases. Here we report a rare case of GBS occurring in a 58-year-old male patient with non-small cell lung cancer (NSCLC) who developed muscle weakness and numbness of the extremities during treatment with chemotherapy combined with KN046, which is a PD-L1 /CTLA-4 bispecific antibody. The patient's symptoms didn't relieve after adopting methylprednisolone and γ-globulin but improved significantly after treatment with mycophenolate mofetil (MM) capsules. Mycophenolate mofetil (MM) is not a routine regimen for GBS, as far as we know, this is the first reported case of ICIs-related GBS who responded well to mycophenolate mofetil other than methylprednisolone or γ-globulin; thus, it provided a new treatment option for patients with ICIs-related GBS.